Liquefaction resistance of fibre reinforced low-plasticity silt - Chegenizadeh, Amin; Keramatikerman, M.; Nikraz, Hamid (Pergamon, 2018)
This study sought to investigate the effect of bulk continuous filament (BCF) on the liquefaction resistance of low plasticity silt by performing a series of cyclic triaxial tests on the reference (unreinforced) and reinforced specimens. The effects of BCF contents and length (BL), relative density (D r ), and effective confining pressure (s' 3 ) on the liquefaction strength of the reinforced specimens were investigated and the results were compared with the reference tests. The results showed that increasing the BCF content improved the liquefaction resistance of the silt. Also, it was noted that increasing the fibre length from 5-mm, to 10-mm and 15-mm respectively, increased the liquefaction resistance of the specimens. The results in the next stage showed that by increasing the relative density (D r ), liquefaction resistance of a reinforced specimen is more pronounced than that of an unreinforced specimen. Finally, investigations on the effect of effective confining pressure (s' 3 ) on the liquefaction resistance of the reinforced specimens showed that increasing the effective confining pressure reduced the liquefaction resistance of the specimens due to suppression of the dilatancy.